Citizen-temple Community - Weinberg, Joel (Journal for the study of the New Testament. Supplement series, 1992)
Often working under severely restricted academic and social conditions, the Latvian scholar Joel Weinberg has made a unique and important contribution to biblical studies. Influenced by Soviet work in ancient Near Eastern history, Weinberg's distinctive approach is in dialogue with scholarship in both Eastern and Western European traditions. This translation brings together seven essays originally published in Russian, then translated and expanded by Weinberg into German. The essays form the basis of what was originally Weinberg's dissertation. Publication of these essays in English will not o.